1996
DOI: 10.1577/1548-8675(1996)016<0324:oesdfe>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Electrofishing Sample Duration for Estimating Relative Abundance of Largemouth Bass in Reservoirs

Abstract: We evaluated the precision of 5–60‐min electrofishing samples for estimating relative abundance of largemouth bass Micropterus salmoides and developed guidelines for optimizing sample duration so that catch rates may be estimated precisely and with the least effort. Catch per hour in the study reservoirs ranged from 16 to 98 and was independent of sample duration. However, the variation in catch per hour among samples of equal duration increased as catch rate and sample duration decreased, resulting in the nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…These results also suggest that, in general, with broader scales of application and evaluation (e.g., basin or lake), effects of habitat manipulations on fish populations are likely to be more difficult to detect. Miranda et al (1996) drew similar conclusions regarding size of experimental units as measured by sampling duration for largemouth bass in reservoirs.…”
Section: Fish Utilization Of Transectsmentioning
confidence: 65%
“…These results also suggest that, in general, with broader scales of application and evaluation (e.g., basin or lake), effects of habitat manipulations on fish populations are likely to be more difficult to detect. Miranda et al (1996) drew similar conclusions regarding size of experimental units as measured by sampling duration for largemouth bass in reservoirs.…”
Section: Fish Utilization Of Transectsmentioning
confidence: 65%
“…This resulted from a reduced level of patchiness and, correspondingly, produced a lower minimum transect number. In an empirical study of largemouth bass sampling, Miranda et al (1996) also found that the number of samples required to reach a given level of precision increased as catch per hour (an indicator of lakewide fish density) decreased and that lake size (as estimated by shoreline length) had little effect on minimum transect number. Similarly, previous studies found that stream length does not significantly influence the effort required to reduce interreplicate variance of CPUE estimates (Lyons 1992;Paller 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The goal of most sampling is to obtain useful, accurate, and precise estimates with the least amount of effort for a given sampling method (Boxrucker et al 1995;Miranda et al 1996). Precision may also be affected by the spatial distribution of the population (location and size of fish patches) and the variability associated with the sampling method (Fiedler 1978;Miranda et al 1996).…”
mentioning
confidence: 99%
“…sand bar) and therefore sampling times were variable because of different habitat lengths. Variation in CPUE tends to increase with sample time duration (Miranda et al ., 1996). To minimize this effect, only electrofishing samples that were between 0·15 and 0·75 h in duration and trammel net samples between 1·5 and 3·5 h were used in the analysis.…”
Section: Methodsmentioning
confidence: 99%